Chemopreventive and Antioxidant Activity of the Chamazulene‐Rich Essential Oil Obtained from Artemisia arborescens L. Growing on the Isle of La Maddalena, Sardinia, Italy. Issue 8 (12th August 2013) - Ornano, Luigi; Venditti, Alessandro; Ballero, Mauro; Sanna, Cinzia; Quassinti, Luana; Bramucci, Massimo; Lupidi, Giulio; Papa, Fabrizio; Vittori, Sauro; Maggi, Filippo; Bianco, Armanodoriano
Abstract The essential oils of Artemisia arborescens growing in Sardinia (Italy), collected during three plant growth stages, i.e., from the vegetative stage to post‐blooming time, were characterized. Moreover, the in vitro antiproliferative and antioxidant activities of the oil isolated from aerial parts collected in February were evaluated. The essential oils belonged to the β‐thujone/chamazulene chemotype, notably with the highest amount of chamazulene (ca. 52%) ever detected up to now in the genus Artemisia and, in general, in essential oils. Quantitative variations in the oil composition were observed as the plant passes from the vegetative to the blooming stage. The oil was tested for its potential tumor cell growth‐inhibitory effect on T98G, MDA‐MB 435S, A375, and HCT116 human cell lines, using the MTT (=3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl‐2H‐tetrazolium bromide) assay. The highest activity was observed on A375 and HCT116 cell lines, with IC50 values of 14 μg/ml. Moreover, the in vitro antioxidant and free radical‐scavenging assays revealed the oil to be an effective scavenger of the ABTS radical cation, with an activity comparable to that of Trolox®. These results support the use of A. arborescens oil for the treatment of inflamed skin conditions. Finally, the composition of the polar fraction of the A. arborescens aerial parts was also examined, and the main component detected was 5‐O‐caffeoylquinic acid, which was identified for the first time in this plant.